ANALISIS SISTEM KERJA WFO DAN WFH TERHADAP KEPUTUSAN KARIER PADA GENERASI Z DI KOTA SUKABUMI - Theodora Zanetha Yovitasari; Bambang Somantri (Jurnal Pijar, 2026)
This study aims to analyze the influence of the Work From Office (WFO) and Work From Home (WFH) work systems on the career decisions of Generation Z in Sukabumi City, based on the phenomenon of high unemployment rates among Generation Z in Indonesia, which raises questions about the factors influencing their opinion on work systems and their impact to career decision-making. Researcher distributed questionnaires to Generation Z respondents aged 15-28 `residing in Sukabumi. This was done as a quantitative data collection method. The sampling technique used purposive sampling, selecting 100 respondents. Data analysis was conducted using SPSS version 25, employing multiple linear regression analysis, along with validity, reliability, and classical assumption tests. The results of the study indicate that: 1) the WFO work system significantly influences Generation Z's career decisions, 2) the WFH work system significantly influences Generation Z's career decisions, and 3) the WFO and WFH work systems simultaneously significantly influence Generation Z's career decisions in Sukabumi City. These findings have implications for companies and related institutions to consider work systems that align with Generation Z's perspectives when designing work policies that support career development.